GBA Variants are associated with a distinct pattern of cognitive deficits in Parkinson's disease. Issue 1 (21st August 2015) - Mata, Ignacio F.; Leverenz, James B.; Weintraub, Daniel; Trojanowski, John Q.; Chen‐Plotkin, Alice; Van Deerlin, Vivianna M.; Ritz, Beate; Rausch, Rebecca; Factor, Stewart A.; Wood‐Siverio, Cathy; Quinn, Joseph F.; Chung, Kathryn A.; et al.
ABSTRACT: Background: Loss‐of‐function mutations in the GBA gene are associated with more severe cognitive impairment in PD, but the nature of these deficits is not well understood and whether common GBA polymorphisms influence cognitive performance in PD is not yet known. Methods: We screened the GBA coding region for mutations and the E326K polymorphism in 1, 369 PD patients enrolled at eight sites from the PD Cognitive Genetics Consortium. Participants underwent assessments of learning and memory (Hopkins Verbal Learning Test–Revised), working memory/executive function (Letter‐Number Sequencing Test and Trail Making Test A and B), language processing (semantic and phonemic verbal fluency), visuospatial abilities (Benton Judgment of Line Orientation), and global cognitive function (MoCA). We used linear regression to test for association between genotype and cognitive performance with adjustment for important covariates and accounted for multiple testing using Bonferroni's corrections. Results: Mutation carriers (n = 60; 4.4%) and E326K carriers (n = 65; 4.7%) had a higher prevalence of dementia (mutations, odds ratio = 5.1; P  = 9.7 × 10 −6 ; E326K, odds ratio = 6.4; P  = 5.7 × 10 −7 ) and lower performance on Letter‐Number Sequencing (mutations, corrected P [ P c ] = 9.0 × 10 −4 ; E326K, P c  = 0.036), Trail Making B‐A (mutations, P c  = 0.018; E326K, P c  = 0.018), and Benton Judgment of Line Orientation (mutations, P c  = 0.0045; E326K, P c  = 0.0013). Conclusions: Both GBA mutations and E326K are associated with a distinct cognitive profile characterized by greater impairment in working memory/executive function and visuospatial abilities in PD patients. The discovery that E326K negatively impacts cognitive performance approximately doubles the proportion of PD patients we now recognize are at risk for more severe GBA ‐related cognitive deficits. © 2015 International Parkinson and Movement Disorder Society